N-acetylcysteine prevents catheter occlusion and inflammation in catheter associated-urinary tract infections by suppressing urease activity - Manoharan, Arthika; Farrell, Jessica; Aldilla, Vina R.; Whiteley, Greg; Kriel, Erik; Glasbey, Trevor; Kumar, Naresh; Moore, Kate H.; Manos, Jim; Das, Theerthankar (Frontiers in Cellular and Infection Microbiology, 2023)
Proteus mirabilis is a key pathobiont in catheter-associated urinary tract infections (CA-UTIs), which is well known to form crystalline biofilms that occlude catheters. Urease activity alkylates urine through the release of ammonia, consequentially resulting in higher levels of Mg 2+ and Ca 2+ and formation of crystals. In this study, we showed that N-acetyl cysteine (NAC), a thiol antioxidant, is a potent urease inhibitor that prevents crystalline biofilm formation. NAC inhibits urease activity of clinical P. mirabilis isolates at concentrations as low as 1 mM, independent of bacterial killing. The study also showed that NAC is bacteriostatic on P. mirabilis, and inhibited biofilm formation and catheter occlusion in an in vitro bladder model. A significant 4-8log10 reduction in viable bacteria was observed in catheters infected in this model. Additionally, biofilms in NAC treated catheters displayed a depletion of calcium, magnesium, or phosphates, thus confirming the absence of any urease activity in the presence of NAC. Interestingly, we also showed that not only is NAC anti-inflammatory in bladder epithelial cells (BECs), but that it mutes its inflammatory response to urease and P. mirabilis infection by reducing the production of IL-6, IL-8 and IL-1b. When combined with ciprofloxacin, NAC also enhances the disruption and killing of mature biofilms. Using biochemical, microbiological and immunological techniques, this study displays the functionality of NAC in preventing catheter occlusion by inhibiting urease activity. The study also highlights NAC as a strong anti-inflammatory antibiofilm agent that can target both bacterial and host factors in the treatment of CA-UTIs.